Fusarium stalk rot in Argentina - Giorda, Laura Maria; Martinez, Maria Jose; Chulze, Sofía Noemí (Iowa State University Press, 2021)
Sorghum crop in Argentina is grown under dryland conditions in several distinct ecological regions. Water déficits may occur during the growing season in ome of these regions. Lodging, root and stalk rot are usually associated with drought stress and photosynthetic stress induced by greenbug damage during grain filling. The fungal isolates most prevalent are species of Fusarium from the Liseola section with Fusarium moniliforme (=Gibberella fujikuroi) as the most serious casual agent of root and grain mold. Greenbug resistance is closely correlated with lodging resistance and is used as an indicator during selection. Research initiated on screening techniques for resistance on early growth stages of the sorghum plant is discussed. Areas of research needed in Argentina are listed.